ChemInform Abstract: Sesquiterpenes from Rhizomes of Cyperus rotundus with Cytotoxic Activities on Human Cancer Cells in vitro. Issue 8 (February 2016) - Ryu, Byeol; Kim, Hye Mi; Lee, Jae‐Seung; Cho, Yoon Jin; Oh, Myung Sook; Choi, Jung‐Hye; Jang, Dae Sik
Abstract: isolation, structure elucidation and cytotoxic activities of two new sesquiterpenes, cyperusol A3 (I) and 3β‐hydroxycyperenoic acid (II), together with three already known sesquiterpenes